Short Communication: Drying methods and diversity of contaminant fungi on coffee beans in South Ogan Komering Ulu District, South Sumatra, Indonesia - Deli Lilia; Nurhayati - Damiri; Zulkarnain Muhammad; Mulawarman Mulawarman (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Lilia D, Damiri N, Zulkarnain M, Mulawarman. 2021. Short Communication: Drying methods and diversity of contaminant fungi on coffee beans in South Ogan Komering Ulu District, South Sumatra, Indonesia. Biodiversitas 22: 1037-1042. South Ogan Komering Ulu District is a Robusta coffee-producing area in South Sumatra. The purpose of this research was to determine the effectiveness of two drying methods on reducing the moisture content of coffee beans by comparing beans dried on tarpaulin and on asphalt roads. The study also assessed the diversity and percentage of fungal contaminants found in coffee beans from each drying method (including OTA-producing fungi). Data was obtained from May until July 2020 from surveys, interviews and samples collected from 30 farmers drying on tarpaulin and 30 farmers drying on the asphalt. The results showed that the moisture content was higher after drying on tarpaulin (13.97% ± 0.55) than on the asphalt road (11.68% ± 0.40). Furthermore, 13 different types of fungi were found for the coffee beans drying on the tarpaulin and 10 types of fungi for those drying on asphalt. In the two methods of drying, it was found that two types of fungi namely Aspergillus niger and Aspergillus ochraceus were potential of producing ochratoxin A (OTA). At the drying on tarpaulin was found mix of more than 93.3% A.niger and A. ochraceus, meanwhile at the drying on asphalt were found mix of more than 90% A.niger and A.ochraceus respectively.